The safe city programme strategies and sustainability in urban tourism environment / Nurin Uzma Eizzaty Noor Eizamly and Faiz Izwan Anuar. - Noor Eizamly, Nurin Uzma Eizzaty; Anuar, Faiz Izwan (Universiti Teknologi MARA Cawangan Selangor, 2020)
Safety and security issues have long been recognized as a major thread to sustainable cities. A higher concern on the safety and security issues have been placed among tourists in urban tourism environment. Hence, the study proposes to investigate the relationship between safe city programme strategies namely design initiatives, target hardening and public awareness and explore the mediating effect of visitors’ satisfaction on the relationship of the safe city program strategies and the sustainability of the programme in the urban tourism environment. The proposed study will assist destination managers, local authorities and policy makers in gaining substantial insight and information to prevent crimes from rising, understand the visitors’ level of satisfaction, and importantly, ensure the safety and security of local residents and tourists in urban tourism environment are always in check.